A conversion strategy to disaggregate asphaltenes via mild hydrotreatment: Theoretical and experimental investigation. (31st December 2022) - Bian, He; Xu, Fang; Wei, Shengchao; Zhang, Huiming; Zhang, Shiguo; Duan, Zunbin; Zhu, Lijun; Xia, Daohong
Graphical abstract: Highlights: A novel strategy of mild hydrotreatment to disaggregate asphaltenes is proposed. Disaggregation mechanism of asphaltenes by mild hydrotreatment is revealed. The stability of asphaltene aggregate is related to the hydrogenation extent. IGMH and SAPT are innovatively performed to clarify interactions of asphaltenes. Abstract: Asphaltenes aggregation is a challenging issue for fully upgrading heavy oils, making the development of efficient liquid-phase disaggregation technologies a high priority. We put forward a feasible strategy to disaggregate asphaltenes via mild hydrotreatment (mild HDT). Mild HDT takes place at low temperature and low hydrogen pressure, differing from traditional hydrotreatment. Quantum chemical calculations suggest that the disaggregation mechanism of the agminated asphaltenes was controlled by the hydrogenation degree, and there is an association between the stability of asphaltene dimers and the hydrogenation extent. Furthermore, a mild HDT experiment at 150 °C and 2 MPa shows that the interchain distance and intersheet distance of hydrogenated asphaltenes increase, and the average number of sheets per crystallite decreases to 3.70 from 6.33. Additionally, both molecular dynamics simulations and aggregation tests show that hydrogenated asphaltene molecules are not prone to reaggregation. This research helps to address the issues derived from asphaltene aggregation.